DINAMICA REPREZENTĂRII SOCIALE. EFECTUL DE CONTEXT - USM ADMIN (Moldova State University, 2007)
Social representations do not emerge on a vacant land. They can be modeled only if there exist a global/ideological context (connected with the ethos of the community) and/or a situational context (connected with the concrete relations we are in at the moment). Building together a social-historical reality, both contexts "wrap up" the human mind, forcing it to process information and develop all sorts of beliefs and visions.